One-Pot Sequential Synthesis of Pyrido[2,3-d]pyrimidine-Fused Isoxazoles: Regio-and Chemoselectivity in Green Solvent - Alizadeh, Abdolali; Hosseini, Seyed Ali (Synthesis, 2025)
A new method has been reported for synthesizing derivatives of isoxazolo[4′,5′:5,6]pyrido[2,3-d]pyrimidine through the reaction of arylglyoxal, 1,3-dimethylbarbituric acid, and 5-aminoisoxazole in water as a green solvent. It involves a one-pot sequential multicomponent reaction, which was carried out in two different approaches (with and without purification of 5-aminoisoxazole). The method forms five chemical bonds and offers advantages such as easy product purification, availability of raw materials, high reaction efficiency, and environmental friendliness. This synthetic strategy has the potential to advance developments in heterocyclic chemistry.
Keywords: arylglyoxal; 1,3-dimethylbarbituric acid; regioselective; chemoselective; hydroxylamine hydrochloride; four-component reaction; environmental sustainability